Spotlight on protein N-terminal acetylation - Rasmus Ree; Sylvia Varland; Thomas Arnesen (Experimental and Molecular Medicine, 2018)
Protein modification: A small change with big effects A chemical modification of protein structure called N-terminal acetylation occurs normally in many circumstances, but is also implicated in diseases including cancers and developmental disorders. It adds an acetyl group, composed of a carbonyl group (C = O) linked to a methyl group (CH3), to the nitrogen atom found at one end of a protein chain. Thomas Arnesen at the University of Bergen in Norway and colleagues review the understanding of this modification and survey the enzymes that carry it out. Acetylation occurs on around 80% of human proteins and affects crucial aspects of their function. These include the stability that determines proteins’ lifetimes inside cells, the three-dimensional structures that proteins fold into, and the interactions between different proteins. Advances in analytical techniques are yielding new insights into the role of N-terminal acetylation in health and disease.